"TRPV1 is a component of the atrial natriuretic signaling complex, and using orally delivered antagonists, presents a valid therapeutic target in the longitudinal reversal and treatment of cardiac hypertrophy and heart failure". Issue 1 (1st January 2019) - Horton, Jaime S.; Shiraishi, Takuya; Alfulaij, Naghum; Small-Howard, Andrea L.; Turner, Helen C.; Kurokawa, Tatsuki; Mori, Yasuo; Stokes, Alexander J.
ABSTRACT: Activation of the atrial natriuretic signaling pathway is intrinsic to the pathological responses associated with a range of cardiovascular diseases that stress the heart, especially those involved in sustained cardiac pressure overload which induces hypertrophy and the pathological remodeling that frequently leads to heart failure. We identify transient receptor potential cation channel, subfamily V, member 1, as a regulated molecular component, and therapeutic target of this signaling system. Data show that TRPV1 is a physical component of the natriuretic peptide A, cGMP, PKG signaling complex, interacting with the Natriuretic Peptide Receptor 1 (NPR1), and upon binding its ligand, Natriuretic Peptide A (NPPA, ANP) TRPV1 activation is subsequently suppressed through production of cGMP and PKG mediated phosphorylation of the TRPV1 channel. Further, inhibition of TRPV1, with orally delivered drugs, suppresses chamber and myocyte hypertrophy, and can longitudinally improve in vivo heart function in mice exposed to chronic pressure overload induced by transverse aortic constriction, reversing pre-established hypertrophy induced by pressure load while restoring chamber function. TRPV1 is a physical and regulated component of the natriuretic peptide signaling system, and TRPV1 inhibition may provide a new treatment strategy for treating, and reversing the loss of function associated with cardiac hypertrophy and heart failure.